Kemampuan Bercerita Anak Prasekolah (5-6 tahun) - Rizqiyani, Revina; Azizah, Nur (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2018)
Abstract: The purpose of this study is to know the knowledge about the language development of preschoolers, especially in the ability to storytelling. The study involved 60 children consisting of 32 boys and 28 girls ranging in age from 5-6 years and there were 4 teachers. The method used is experiment with pretest-postest control group design. Qualitative descriptive data were obtained from teacher interviews. Quantitative data obtained from the observation sheet of storytelling ability. Children do story-telling activities using a wordless picture book for the experimental group and a picture book with text for the control group. This research reveals that with a wordless picture book is more effective to improve the ability to tell the story of preschoolers than the story books in general. Children are more adept at choice of words and gestures through the images they see.Â Â